Engineering modeling languages : turning domain knowledge into tools /: turning domain knowledge into tools. (2016) - Combemale, Benoit; France, Robert; Jézéquel, Jean-Marc; Rumpe, Bernhard; Steel, James; Vojtisek, Didier
No abstract available